Secure Communication with Physical Layer Coding Scheme - Chen, Jong-Shin; Yang, Cheng-Ying; Yao, Jenq-Foung JF; Yen, Chin-En; Hwang, Min-Shiang (IEEE International Conference on Consumer Electronics-China (Online), 2023)
For a secure communication, it enables the destination could successfully release the authentic information from the sender. At the meantime, a secure system protects the transmitted information from the eavesdroppers. Traditionally, the encryption, authorization and authentication schemes could be employed for protecting the eavesdroppers. However, the unexpected attacks have been continuously developed. It could not be avoided for the undesired attacks. According to Shannon's perfect communication, there exists an error-free cryptogram that could protect for the attacker. Hence, based on the secrecy rate, it is expected that the secure communication could be practical with physical-layer coding scheme. Besides, the coding scheme is not only to obtain a critical level of security, but also to achieve a lower decoding error. For a security concern, increasing the secrecy rate leads a higher level of security ability. However, it might suffer the system performance without bandwidth efficiency. Hence, the tradeoff between the security level and coding rate is important to lead a secure communication.